'Being Maasai' in Markets and Trade: The Role of Ethnicity-based Institutions in the Livestock Market of Northern Tanzania. (1st January 2017) - Allegretti, Antonio
Abstract : The strong awareness of cultural and ethnic identity among the Maasai of Tanzania is very well known, as are the recent diversification and marketintegration processes that the Maasai are undertaking. It has seldom been highlighted, however, how the first is involved in the second: i.e. whether and how being Maasai 'matters' in market exchange. Here I argue that practices, values and social relationships underlying Maasai ethnic identity are crucial when applied to the realm of the livestock market. They are part of the structural organisation of the livestock market in that they aid Maasai market actors in minimising risk and costs, maximising returns, and dealing with the constraints of the market. A better understanding of the local dynamics of market exchange has important policy implications, in that it can open policymakers' eyes to the benefits of the traditional pastoral system for raising livestock.